CORPORATE LIABILITY FOR DEFECTIVE PRODUCT - Daniel Surya Partogi; Ghansham Anand (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research revolves around the accountability of producers to consumers for products that are not suitable for use. The purpose of this study is to determine and analyze the forms of producer accountability towards their consumers in regards to products that are not qualified for sale. This study also seeks to analyze the legal remedies of consumers against producers on products that cause them losses. The researcher applied normative research method. This research shows that the rights and obligations of producers are often infringed and the victims are consumers. Consumers sometimes do not get the goods they have bought as advertised through the commercials; as an example, the products might not be suitable for use, and in some cases, consumers might be harmed. This study concludes that the responsibility of producers to consumers on defective products is to compensate the losses suffered by consumers due to their unqualified products